Disjunctive Antecedents for Causal Models - Günther, Mario (Proceedings of the Amsterdam Colloquium, 2025)
Sartorio [4] argues convincingly that disjunctive causes exist. To treat disjunctive causes within Halpern and Pearl [2]’s framework of causal models, we extend their causal model semantics by disjunctive antecedents and propose a refinement of their definition of actual causation.